A study on the collection of Jawi manuscripts on the Naqshbandis at the National Library of Malaysia - Nasir, Mohamad Nasrin (Penerbit UKM, 2023)
A study on the manuscripts regarding the Naqshbandi Sufi Order found at the National Library of Malaysia.